Development of the formalized scheme of chemical conversions in the process of vacuum gas oil hydrotreating for the process modelling; Catalytic Hydroprocessing In Oil Refining (STS-HydroCat - 2021) - Belinskaya N. S. Natalia Sergeevna; Ivashkina E. N. Elena Nikolaevna; Afanasjeva D. A. Darjya Aleksandrovna; Krivtsova N. I. Nadezhda Igorevna; Vymyatnin E. K. Evgeny Konstantinovich; Arkenova S. B. Sania Bolatovna; Kaliev T. A. Toleubek Arystanbekovich (2021, 2021)
Title screen